Towards the Establishment of a Capability Model for Open Access Repositories - Oliveira, Raul Donaire Gonçalves (2023)
Education is evolving through the years. Computers, mobile devices and the growing access to the Internet are playing a big role in these changes. Open Educational Resources (OERs) emerge in this context, trying to gather the strengths of the modern and technological society in order to improve the overall quality of global education. OERs are any type of teaching, learning and research materials that can be reached in the public domain or have been published under one of the intellectual property licenses. OERs enable the learning process to be open and flexible, providing suitable opportunities and adapted to individual needs, promoting overall improvement of teaching abilities, reducing the global cultural gap, minimizing the dependence of commercial books and helping students from poor communities. Universities, educational institutions and others non-profit organizations often share their OER content through Open Access (OA) repositories. However, there is some concerns about the quality assurance these OA repositories; most institutions only uses their brand and reputation to persuade their students that their resources have an adequate excellence degree. In a different but related perspective, Maturity and Capability Models emerged as an interesting approach for quality assurance. The main idea is to improve the industry performance through incremental and structured enhancement, increasing the competence of organisations in achieving strategic objectives. Maturity and Capability Models were originally developed for software companies, but nowadays they are often tailored for other fields, specially on the education area. Although there are indeed several educational Maturity and Capability models, none of them are specifically related to OERs. In this context, the main goal of this Masters work is to verify whether a capability model, specifically tailored for OERs sharing initiatives, can improve the academic trust in the related processes of such initiatives. The model should support students searching for OERs, educators that want to share their own resources and maintainers searching for points of improvement in their repositories. Our research indicate which qualities must be considered when characterizing an Open Access Repository. As a result we developed a Capability Model for Open Access Repositories, named CM-OAR, aiming at the enhancement of the trustworthiness of these repositories, by solving, or at least minimizing, the concerns about its quality assurance.